Towards a humanistic narrative about art: reflections on Emmanuel Levinas and Ernst Bloch - Terreblanche, Salomon (University of the Free State, 2007)
This article explores the possibilities of a humanistic narrative about art with special reference to the thought of Emmanuel Levinas and Ernst Bloch. Throughout the article it is shown how Levinas’s and Bloch’s respective interpretations of art are connected with their theories of ontology. Levinas understands being as a neutral and indifferent manifestation of reality. In his phenomenological analysis of art Levinas appeals to examples from modern art in particular and emphasises that artworks withdraw from the ‘light’ of being, which is to say, artworks refuse intelligible description in language. For Bloch, by contrast, being essentially carries an unrealised promise in the germ. Bloch hermeneutically explores the ‘pre-appearance of utopia’ and human happiness that are portrayed and symbolised by religious, pre-modern and early modern art in particular. Towards the end of the article an interpretation of prophetic hope is put forward with reference to Levinas’s and Bloch’s work, in an attempt to overcome the limitations of both authors with respect to the possibilities of a humanistic narrative about art.

Hierdie artikel verken die moontlikhede van ’n humanistiese kunsnarratief met spesiale verwysing na die denke van Emmanuel Levinas en Ernst Bloch. Daar word deurgaans aangetoon hoe Levinas en Bloch se onderskeie interpretasies van kuns verband hou met hulle synsopvattings. By Levinas word die syn as ’n neutrale en onverskillige manifestasie van die werklikheid beskou. In sy fenomenologiese analise van kuns maak Levinas in die besonder gebruik van voorbeelde uit moderne kuns en beklemtoon hy dat kunswerke hulle onttrek aan ‘lig’, en dus beskrywing en verstaanbaarheid in taalgebruik weerstaan. Volgens Bloch daarenteen dra die syn wesenlik ’n onvervulde belofte in die kiem. Bloch maak hermeneuties gebruik van die idee dat veral religieuse, premoderne en vroegmoderne kuns ’n voorafskaduwing van die steeds onvervulde menslike geluk vasvang. Teen die einde van die artikel word ’n interpretasie van profetiese hoop aan die orde gestel na aanleiding van die werk van Levinas en Bloch, en word aangevoer dat die beperkinge van albei denkers ten opsigte van die moontlikhede van ’n humanistiese kunsnarratief daardeur te bowe gekom kan word.
Keywords: Lévinas, Emmanuel; Bloch, Ernst; Theories of ontology; Humanistic narrative